Strategi Kegiatan Keagamaan dalam Membentuk Karakter Religius Siswa di SMKN 4 Malang - Isroilliyah, Isroilliyah (SAP (Susunan Artikel Pendidikan), 2024)
This research aims to explore and analyze the religious activity strategies implemented at SMKN 4 Malang to form students' religious character. Using a qualitative approach, this research examines various aspects of strategies involving a holistic approach, active student participation, innovation in learning, collaboration with parents and the community, strengthening ethics and morals, as well as continuous monitoring and evaluation. The research was conducted using descriptive analytical research with qualitative research, while for data collection techniques, the researcher used observation and interview methods. The research results show that SMKN 4 Malang has succeeded in combining these elements to create an integrated approach to forming students' religious character. A holistic approach ensures that religious learning is not limited to the classroom but is also integrated into extracurricular activities and the overall school environment. Students' active participation in religious activities helps build personal involvement and a deeper understanding of religious values. This research also highlights the importance of continuous monitoring and evaluation to ensure the sustainability and effectiveness of this strategy in shaping students' religious character. Thus, the implementation of religious strategies at SMKN 4 Malang makes a positive contribution to the formation of a young generation that is morally and spiritually responsible.